Sistema de control interno y su efecto en la gestión operacional del centro médico de especialidades club de leones de Quevedo, año 2017 - Juez Zambrano, Marcela Valeria (2018)
The investigation in the Medical Center of Specialties Club of Lions of the City of Quevedo, determines that its main problem lies in the limited internal control of operational activities, since there is inadequate handling of medical equipment, supplies of materials and other necessary resources for the development of internal functions, which is why we analyze the main weaknesses in the management process that cause poor attention to users who attend the aforementioned institution; The focus of the research process is based on a qualitative and quantitative analysis of the internal processes that are carried out in reference to internal control, operational management and institutional planning. The research methodology developed to obtain relevant data of the problems presented in the management is as follows: Type of qualitative and quantitative research, where primary and secondary sources of information were consulted, in addition, the investigative technique of the interview was applied Medium of an internal control questionnaire addressed to three segments: Administration Area, Administrative Technical Council and General Coordination, where the results denote the absence of an institutional strategic planning, flow charts of medical attention and administrative processes, little control of the implements local doctors and inadequate attention to users; Probably the presence of these institutional weaknesses is due to the absence of professional experts in administration who can elucidate problems of planning and control of administrative, financial and operational activities. Keywords: Internal Control, Management, Operational Activities, Processes, Planning